STUDI LITERATUR: PEMANFAATAN EKSPOR SCRATCH KE HTML5 APLIKASI MOBILE SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF BAGI PENDIDIK - Risman; Denni, Irdam; Suprihadi, Dudi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study adopts a literature review approach aimed at synthesizing and critically analyzing existing scholarly works relevant to the research topic focuses on transformation of Scratch projects into HTML5 format as part of a strategy for developing interactive learning media based on mobile applications. In this conversion process, the HTMLifier platform is utilized to convert Scratch files with the (.sb3) extension into HTML5 format. Next, the converted files are developed into Android applications through the Website 2 APK Builder Pro service. This research employs the Systematic Literature Review (SLR) methodology, which involves a structured and methodical sequence of procedures designed to examine the literature related to the adaptation of Scratch-based educational projects into mobile applications that are attractive, easily accessible, The selected studies were analyzed based on their methodological rigor and how well they address issues that are pertinent to present-day requirements digital learning. The findings of the research suggest that this method represents a applicable solution in the creation, distribution, and utilization of digital learning media, especially for teachers or education practitioners who do not have a technical background in programming. This conversion process not only simplifies the technical stages but also expands the potential the implementation of Scratch within the framework of mobile learning. The integration between Scratch and HTML5 encourages technology-based learning innovation with a low-code approach, while strengthening the role of educators or teachers in creating educational, creative, and inclusive interactive materials that are adaptive to current developments in educational technology.